Dexamethasone (DXM)‐Coated Poly(lactic‐co‐glycolic acid) (PLGA) Microneedles as an Improved Drug Delivery System for Intracochlear Biodegradable Devices. Issue 11 (8th August 2021) - Pawley, Devon C.; Goncalves, Stefania; Bas, Esperanza; Dikici, Emre; Deo, Sapna K.; Daunert, Sylvia; Telischi, Fred
Abstract: Uniform drug delivery techniques are challenging to develop for the inner ear due to the complexity of the cochlear anatomy. A promising solution is the use of biodegradable polymers because the continuous release of therapeutics without introducing toxic compounds is desirable. Using a microneedle approach lends the polymeric microneedle the capability to be placed inside of the scala tympani, releasing drugs overtime. Poly(lactic‐ co ‐glycolic acid) (PLGA) microneedles is prepared by dissolving dimethyl sulfoxide with either a) Rhodamine B, to study the drug release profile in vitro, b) FM1‐43, to study the drug release profile in vivo, or c) dexamethasone (DXM), to protect hair cell (HC) loss in vivo. The Rhodamine B studies show that the dye begins release from the microneedles within 30 min. The ototoxicity assessment of the DXM‐coated microneedles in vitro shows a significant reduction of HC losses when compared to control microneedles in an ototoxic environment. In vivo data show reduced hearing threshold for animals treated with DXM‐infused microneedles, providing a proof of concept of the methodology developed. Drug‐infused polymeric microneedles provide a promising method to deliver DXM to the inner ear over controlled periods of time protecting hair cells, thus minimizing hearing loss (HL). Abstract : Custom designed drug‐infused polymeric microneedles provide a novel platform to deliver therapeutic molecules uniformly over time without introducing toxic foreign compounds to the body. For hearing loss applications, following in vitro biocompatibility and ototoxicity assessments, the microneedles are placed inside of the scala tympani of rats for 1 week and demonstrate hair cell protection in the cochlea.